2017
DOI: 10.2147/dddt.s130320
|View full text |Cite
|
Sign up to set email alerts
|

Ten years' clinical experience with biosimilar human growth hormone: a review of efficacy data

Abstract: In 2006, the European Medicines Agency (EMA) approved Omnitrope® as a biosimilar recombinant human growth hormone (rhGH), on the basis of comparable quality, safety, and efficacy to the reference medicine (Genotropin®, Pfizer). Data continue to be collected on the long-term efficacy of biosimilar rhGH from several on-going postapproval studies. Particular topics of interest include efficacy in indications granted on the basis of extrapolation, and whether efficacy of growth hormone treatment is affected when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In their reviews, Lopez-Siguero et al [ 17 ] and Borras-Perez et al [ 18 ] summarised 10 years of experience with the use of biosimilar rhGH and reported that switches between the reference product or another rhGH-containing product and the biosimilar did not affect therapeutic efficacy or safety. They analysed the results of phase III and IV trials, as well as those of an ongoing post-approval study in patients with growth disorders in the course of growth hormone deficiency or small for gestational age.…”
Section: Effect Of Switching On Therapeutic Efficacy and Safety – CLImentioning
confidence: 99%
“…In their reviews, Lopez-Siguero et al [ 17 ] and Borras-Perez et al [ 18 ] summarised 10 years of experience with the use of biosimilar rhGH and reported that switches between the reference product or another rhGH-containing product and the biosimilar did not affect therapeutic efficacy or safety. They analysed the results of phase III and IV trials, as well as those of an ongoing post-approval study in patients with growth disorders in the course of growth hormone deficiency or small for gestational age.…”
Section: Effect Of Switching On Therapeutic Efficacy and Safety – CLImentioning
confidence: 99%
“…Hence, post-marketing trials of biosimilar GH are necessary. [ 16 ] In Indian markets, at least two biosimilar GH preparations are available namely Eutropin and Headon. In this study, the innovator GH used was 'Norditropin' which was a Somatropin (rDNA origin) injection, while, the biosimilar GH used was the injection 'Headon' which is synthesized from a strain of Escherichia coli (Recombinant DNA technology).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Very recent data from various long-term studies worldwide also suggest that the use of biosimilar GH in comparison to the innovator GH is efficient and safe in GHD children. [ 16 ] However, such data in other growth disorders are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Any disorder in the secretion of hGH in childhood or adolescence can lead to a variety of diseases including gigantism, acromegaly, and dwarf diseases [2,3]. hGH has been used in clinics since 1985 to treat a variety of children as well as adults hGH-related disorders, including Prader-Willi syndrome, chronic renal insu ciency, Turner syndrome, AIDS-related wasting, fat accumulation associated with lipodystrophy in adults [4,5]. Furthermore it may also be associated with some metabolic complications and even mellitus diabetes [6].…”
Section: Introductionmentioning
confidence: 99%